Epidemiology of Pig Tuberculosis in Argentina - Barandiaran, Soledad; Marfil, María Jimena; Capobianco, Guillermo; Pérez Aguirreburualde, María Sol; Zumárraga, Martín José; Eirin, María Emilia; Cuerda, María Ximena; Winter, Marina; Martínez Vivot, Marcela; Perez, Andres Maximiliano; La Sala, Luciano Francisco (Frontiers in Veterinary Science, 2021)
Bovine tuberculosis (TB) is a disease caused by the Mycobacterium bovis which is endemic in livestock in most Latin American countries. Traditionally, TB control programs are costly and targeted to cattle, largely disregarding other species such as swine and wildlife. In Argentina, disease prevalence in commercial pigs is comparable to that observed in cattle, suggesting the need for efficient control programs to manage the disease in both species. Additionally, outdoor production systems, which are commonly practiced in Argentina, allow the interaction between livestock and wildlife such as wild boar (Sus scrofa), which is consider a natural host of the disease. Here, we evaluated the TB dynamics in the commercial pig population and identified farm-level variables associated with Mycobacterium bovis confirmation in tuberculosis-like lesions (TBL) collected in abattoirs. Additionally, we assessed the potential transmission between pigs, cattle, and wild boar based on genotypes identified in those species. Multivariable logistic regression models were used to assess the association between farm-level epidemiological variables (location, farm size, and co-existence with cattle and goats) and TB confirmation in TBL samples. Results showed that the odds of TB dropped 0.3% and 0.6% for every unit increase in the number of sows when cattle were present or absent in the farm, respectively. Pigs shared 60% (18/30) of the reported genotypes with wild boar and cattle, suggesting transmission of the disease among those species. These results provide novel information about the molecular diversity of M. bovis strains in commercial pigs in Argentina and proposes the potential relevance of a multi-host system in the epidemiology of TB. Statistical models presented here may be used in the design of a low cost, abattoir-based surveillance program for TB in the pigs industry in Argentina, with application to other settings with similar epidemiological conditions.